An analogue circuit to study the forced and quadratically damped Duffing oscillator. (2017) - Singh, Udayprakash Raghunath; Purohit, Ghanshyam; Sharma, Anjali; Patidar, Vinod
In this communication we study the forced and quadratically damped Duffing oscillator system experimentally through an analogue circuit. For this purpose we design a circuit and observe its dynamical behaviour under various sets of control parameters and also compare the experimental results with the numerical simulation results.